Different distribution of free and bound phenolic compounds affects the oxidative stability of tea seed oil: A novel perspective on lipid antioxidation. (July 2020) - Wang, Xiaoqin; Contreras, María del Mar; Xu, Dunming; Xing, Chen; Wang, Lijuan; Yang, Daomao
Abstract: Bound phenolic compounds have been widely investigated in food from plants, while research on vegetable oils is limited. Thus, to comparatively analyse free and bound phenolic compounds in a lipid system, different distributions of free and bound phenolic compounds were prepared by exogenous addition of chemical standards to model tea seed oil in this work. For that, the phenolic composition was quantified with UHPLC-QqQ-MS/MS, and the antioxidant capacity was evaluated by the DPPH assay and the Rancimat method. After pre-optimisation of concentrations, the results showed that the oil sample contained 12.3% bound phenolic compounds after incubation for 6 h, higher than the other samples (0, 2, 4, 8, 10 and 12 h) with equal addition. This sample also had a longer reduction time during Rancimat oxidation, corresponding to the higher total DPPH radical scavenging capacity. Further, docking, molecular dynamics and quantum mechanics analysis revealed that intermolecular forces might account for binding forms between phenolic compounds and glycerides, including hydrogen bonds and hydrophobic interactions. In addition, the structure-activity relationship of bound phenolic compounds was explored tentatively. Conclusively, bound phenolic compounds in vegetable oil, probably formed by intermolecular interactions, enhanced antioxidant capacity, a novel perspective on the antioxidation in lipids. Highlights: Different distributions of free and bound phenolic compounds were obtained. Bound phenolic compounds showed stronger antioxidant capacities. Intermolecular interactions might occur between phenolic compounds and glycerides. Binding might affect the molecular conformation of phenolic compounds.